The Role of Social Commerce Trust and Satisfaction on TikTok Consumer Purchasing Behavior - Nur Islah Prestyasih; Sri Rahayu Hijrah Hati (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The rapid rise of social commerce, especially on platforms like TikTok, has transformed how consumers engage in online shopping. This study investigates the influence of social commerce trust and satisfaction on purchasing behavior among Indonesian TikTok users, using trust transfer theory and socio-technical theory. A quantitative approach was employed, involving 271 valid respondents who had shopped on TikTok Shop within the past three months. Data were collected through an online questionnaire and analyzed using SmartPLS 3 with a disjoint two-stage approach. The results show that social support, customer review quality, and surface credibility significantly influence social commerce trust, while social media activities do not. Additionally, trust positively affects satisfaction, which in turn enhances purchasing behavior. Surface credibility also directly impacts satisfaction. These findings underscore the importance of credible user-generated content and peer interactions in building consumer trust and satisfaction in social commerce. Practically, businesses can leverage customer reviews, social support, and interface credibility to increase user engagement and conversion rates. The study contributes theoretically by integrating multi-dimensional trust constructs and practical strategies for improving TikTok-based commerce. Future research should explore other age groups, platforms, and broader trust dimensions for a more comprehensive understanding of social commerce behavior.